Development of Higher Education Key Performance Indicator Monitoring System using Rapid Application Development Method - Adi Widianto; Laurentinus Laurentinus (STEKOM PRESS, 2026)
Key Performance Indicators (KPIs) have a very essential role in higher education institutions in order to maintain the quality standards and to meet the requirements of the accreditation. But manual input and tracking typically results in data silos, data loss and delayed reporting. Furthermore, the system must be integrated with the subsystems that have already been built, which makes the development process longer and more complex. The purpose of this project is to design a university web-based KPI monitoring system by using Rapid Application Development (RAD) method to increase efficiency and reduce data loss. This choice is done because it allows a fast implementation in a real environment with an already existing subsystem. It started development in June 2025 and continued through August. The user input was looped as per criteria. The KPI tracking system has been implemented in one semester already. RAD has already proven to be the right methodology, as it achieved the goal of fast implementation and satisfied functional requirements.